Kelly, Kim. Photograph of Sheila and Bill Kelly on their wedding day. - Heritage NL (1968)
Kim Kelly provided a picture of Sheila and Bill Kelly on their wedding day, 15 June 1968. The two are standing together in front of a stage with a blue curtain, and Sheila is holding a bouquet of red and white flowers.